SALT-SENSITIVITY IN HEALTHY NORMOTENSIVE MEN IS ASSOCIATED WITH IMPAIRED BAROREFLEX SENSITIVITY. (June 2022) - Oppelaar, Jetta J.; Bouwmeester, Thomas A.; Silova, Anastasia A.; Collard, Didier; Wouda, Rosa D.; Rorije, Nienke M.G.; Engberink, Rik H.G. Olde; Van Den Born, Bert-Jan H.; Vogt, Liffert
Abstract : Objective: Blood pressure (BP) responses to Na+ intake show great variability, discriminating sodium sensitive (SS) from salt resistant (SR) individuals. The pathophysiology behind salt-sensitivity is still not fully elucidated. A pivotal role for the sympathetic nervous system to BP increase after sodium loading is suggested. Therefore, we aimed to investigate the effect of the sympathovagal balance on Na+-induced BP effects and if Na+-induced effects on sympathetic activation contribute to salt-sensitivity. Design and method: We performed a randomized cross-over study in 31 young healthy men with normal BMI and eGFR. Subjects followed both an 8-day low Na+ diet (LSD, < 50mmol/d) and high Na+ diet (HSD, > 200mmol/d), in 18 subjects the diets were extended to 14-days. SS was defined as an increase of three or more mmHg standardized measured office MAP after HSD. Cardiac-output (CO) and cross correlation baroreflex sensitivity (xBRS) were measured with continuous non-invasive finger photoplethysmography. Systemic vascular resistance (SVR) was calculated as the ratio of MAP by CO. Results: After HSD, SS men (19%) showed a mean 6.2 (±2.1 SD) mmHg increase in MAP. No absolute differences in Na+-induced effects on CO and SVR could be observed between groups. After HSD, xBRS was 34% lower in SS men compared to SR men (Fig1A). Sodium loading resulted in a mean xBRS decrease of 3.4 (±6.5 SD) ms/mmHg in SS men, whilst xBRS increased with 2.3 (±6.3 SD) ms/mmHg in SR men (p = 0.06). HSD xBRS values were significantly correlated with Na+-induced BP changes in the complete group when corrected for age and BMI (Fig1B). Conclusions: Salt-sensitivity of BP in young normotensive men seems to be predominantly driven by changes in sympathovagal balance. The significant correlation between xBRS and delta BP further suggests a continuous relation between sympathetovagal balance and salt exposure. Further studies are needed to unravel pathophysiological mechanisms underlying Na+-effects on sympathetic regulation.